Development of students' critical thinking as the development of their functional literacy - Vera M. Zhurakovskaya; Sergey V. Krivykh (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Indicators of the quality, competitiveness of general education are the educational results of students recognized in the world, corresponding to functional literacy, which includes, among other things, critical thinking of students. The purpose of the paper is to develop a technique for the development of students' critical thinking Critical analysis of the text and its rationale, a description of its practical application in the educational practice of a general education institution. Research methods include methods of theoretical and empirical research. The paper proposes the technique Critical analysis of the text, represented by a new list of questions, the rationale for which is carried out on the basis of 4 laws of logic, the criteria for selecting the content of education, which provide the possibility to develop techniques for the development of critical thinking of students. An example of using the technique "Critical analysis of the text" at the lesson of Conversations about the important issues is also given. An analysis of the achievements of experimental work related to the use of techniques for the development of critical thinking of students in the educational process made it possible to establish an increment in the experience of critical thinking of students, which gave reason to consider the developed techniques effective. The scientific novelty of the study includes the method of "critical analysis of the text", represented by a new list of questions developed on the basis of the theories of critical thinking and logic. The theoretical significance of the study is related to the substantiation of the list of questions for the "Critical analysis of the text" technique, carried out on the basis of the argumentation theory, with the development of criteria for selecting the content of education, on the basis of which it is possible to design multi-level tasks for the development of students' critical thinking. The practical significance of the results of the study is shown in the given example of using the method "Critical analysis of the text" in educational practice, in particular at the lesson of "Sport and Politics" ("Talk about the important"). The Critical Analysis of the Text method developed in the study, which determines the development of critical thinking of students, enriches the theory of pedagogical design and opens up new opportunities for its further development.